Experiences of Transgender Men in Accessing Care in Gynecology Clinics [24G]. (May 2018) - Frecker, Helena; Scheim, Ayden; Leonardi, Mathew; Yudin, Mark
Abstract : INTRODUCTION: Transgender, or "trans, " individuals face barriers to accessing medical care, however little is known regarding trans men's experiences in accessing gynecologic care in particular. This study sought to determine if trans men in Ontario avoid presenting for gynecologic care and to gain understanding of their experiences in accessing this care. METHODS: Trans men ≥18 years old and living in Ontario were invited to participate in an online questionnaire. The study poster with questionnaire URL was distributed in both physical and online spaces frequented by the trans community. RESULTS: Of 89 respondents, 84/87 (97%) reported using a pronoun different from that associated with their birth-assigned gender, 71/87 (82%) reported current or past testosterone use, and 46/85 (54%) had undergone gender confirming surgery. 72/78 (92%) felt anxious about seeking gynecologic care and 43/79 (54%) had avoided attending gynecologic care settings because they were trans, citing the following reasons: encountering gendered forms (50%), sitting in a waiting room with cis women (54%), being misgendered (59%), having to educate providers (70%), and undergoing the gynecologic exam itself (86%). Many respondents found the gynecologic exam physically (60%) and emotionally (75%) distressing. Respondents endorsed options for an improved exam experience, including providers using gender non-specific language (85%), explaining each step before it occurs (55%), and having a support person present (47%). CONCLUSION: This study has highlighted areas for improvement in care provision that can be adopted by gynecologic care providers in order to make the experiences of trans men more inclusive, safe, and positive.